Societal and economic factors associated with COVID-19 indicate that developing countries could suffer the most - Selvitella, Alessandro Maria; Foster, Kathleen Lois (Technium Social Sciences Journal, 2020)
Most of the research related to the COVID-19 pandemic deals with the biological and epidemiological factors which have driven the spread of the coronavirus around the globe. In this paper, we analyse how societal and economic variates relate to the number of cases and deaths across countries, via machine learning methods. Our findings recommend focusing our attention on developing countries where the healthcare system might suffer the most.